Strategie innowacji w przedsiębiorstwach - Jasińska, Alicja (Innovation strategies of enterprises, 2007)
The article presents the essence of Resource-based View of a company. The author explains issue of resources, skills, competences as well as points of the importance of some of the assets of a company on the global market. The author tries to proveby, that nowadays intellectual capital is becoming one of the key factors for achieving success modern company
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 109-119